Microstructural investigation of M2 high speed steel produced by selective laser melting: microstructural investigation of M2 high speed steel - Leong, Kah Fai (2013)
In SLM, a high energy density is applied by a laser to locally melt layers of metallic powder particles in order to create functional parts. This high energy intensity and additive process character create a specific/unique microstructure. The solidified melt pools in HSS M2 SLM parts are observed to consist of two distinct zones next to the heat affected zone. The first zone, at the bottom of the melt pool, consists of very fine cells and columnar dendrites and has a hardness of 655±80Hv0.1. The other zone contains acicular martensite and has a hardness of 859±80Hv0.1 which is already similar to the hardness of conventionally produced and heat treated HSS M2. Furthermore, the relative amount of these two zones is observed to be dependent on the scan velocity of the laser and hence can be controlled during the SLM process.